Gambaran Pembiayaan Pendidikan pada Jenjang SMP Kabupaten Deli Serdang Di Masa Pandemi - Lidya Ardiyan; Eka Daryanto; Osbert Sinaga (CV. Syntax Corporation Indonesia, 2022)
This research aims to describe the difference in education financing in education financing during the pandemic and after the pandemic in Deli Serdang Junior High School. The four schools that are the location of this research are SMPN 3 Lubuk Pakam, SMPN 1 Tanjung Morawa, SMPN 3 Labu Beach, and Maitreyawira Junior High School. This study is comparative descriptive research. The informant of the study is the principal and treasurer of the school. The data collection method used is in the form of online instrument filling and telephone interviews. The results showed that the financing of education at Junior High School in Deli Serdang Regency already followed national education financing standards. It was also found that there was no significant difference in the cost of education in the pandemic period and after the pandemic. Financing in Public Schools still comes from one source, namely BOS funds, while education financing in private schools comes from the contribution of foundations and SPP students